Setting a research agenda for interprofessional education and collaborative practice in the context of United States health system reform. Issue 1 (2nd January 2016) - Lutfiyya, May Nawal; Brandt, Barbara; Delaney, Connie; Pechacek, Judith; Cerra, Frank
ABSTRACT: Interprofessional education (IPE) and collaborative practice (CP) have been prolific areas of inquiry exploring research questions mostly concerned with local program and project assessment. The actual sphere of influence of this research has been limited. Often discussed separately, this article places IPE and CP in the same conceptual space. The interface of these form a nexus where new knowledge creation may be facilitated. Rigorous research on IPE in relation to CP that is relevant to and framed by health system reform in the U.S. is the ultimate research goal of the National Center for Interprofessional Practice and Education at the University of Minnesota. This paper describes the direction and scope for a focused and purposive IPECP research agenda linked to improvement in health outcomes, contextualized by health care reform in the U.S. that has provided a revitalizing energy for this area of inquiry. A research agenda articulates a focus, meaningful and robust questions, and a theory of change within which intervention outcomes are examined. Further, a research agenda identifies the practices the area of inquiry is interested in informing, and the types of study designs and analytic approaches amenable to carrying out the proposed work.